2017
DOI: 10.1007/s11695-017-2574-0
|View full text |Cite
|
Sign up to set email alerts
|

Large Buffering Effect of the Duodenal Bulb in Duodenal Switch: a Wireless pH-Metric Study

Abstract: IntroductionBariatric procedures result in massive weight loss, however, not without side effects. Gastric acid is known to cause marginal ulcers, situated in the small bowel just distal to the upper anastomosis. We have used the wireless BRAVO™ system to study the buffering effect of the duodenal bulb in duodenal switch (DS), a procedure in which the gastric sleeve produces a substantial amount of acid.MethodsWe placed a pre- and a postpyloric pH capsule in 15 DS-patients (seven men, 44 years, BMI 33) under e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In our study, we reported a low incidence of MU, which aligns with the limited available research reporting MU rates ranging from 0.2% to 1.9% in patients following DS [4,[14][15][16][17]. This low occurrence of MU in DS could be attributed to the preservation of the pyloric sphincter, which plays a crucial role in buffering and neutralizing the substantial amount of gastric acid that passes into the small bowel after the procedure [18]. In fact, the alkaline mucus produced by the Brunner's glands in the duodenum plays a role in protecting the ileal mucosa from the high acidity as well as the reduced parietal cell mass from the sleeve gastrectomy [7].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we reported a low incidence of MU, which aligns with the limited available research reporting MU rates ranging from 0.2% to 1.9% in patients following DS [4,[14][15][16][17]. This low occurrence of MU in DS could be attributed to the preservation of the pyloric sphincter, which plays a crucial role in buffering and neutralizing the substantial amount of gastric acid that passes into the small bowel after the procedure [18]. In fact, the alkaline mucus produced by the Brunner's glands in the duodenum plays a role in protecting the ileal mucosa from the high acidity as well as the reduced parietal cell mass from the sleeve gastrectomy [7].…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study with wireless pH-metry, we were able to show that the duodenal bulb has a buffering effect, reducing the time with pH < 4 from 59% in the gastric sleeve to 14% distal to the pylorus. This could theoretically result in lower incidence of MU at the duodeno-ileostomy after DS [25].…”
Section: Introductionmentioning
confidence: 99%
“…Below the duodenoileostomy, a more or less neutral environment (5.79 (4.75-7.58)) was observed with an acidic pH < 4 measured during 13.0% (range: 0.0-34.6) of time. These findings suggest that the Brunner's glands located in the duodenal bulb neutralize the acidic content of the gastric sleeve via the secretion of alkaline mucus (38). Whether the buffering effect of the duodenal bulb neutralizes the acidic content in case of a SG remains to be understood.…”
Section: Gastrointestinal Acid Secretion After Sleeve Gastrectomy and Roux-en-y Gastric Bypassmentioning
confidence: 91%
“…Due to the absence of SG studies, clinical studies in patients with duodenal switch provide some first insights. Pre-pyloric pH monitoring during 24 hour indicated the preservation of the acidic gastric environment (pH: 2.66 (Interquartile range of 1.74-5.81)) with an acidic pH < 4 measured during the majority of time (68.7%) (38). Whether these findings can be directly translated to patients with a SG remains unsure due to the difference in surgical procedure.…”
Section: Gastrointestinal Acid Secretion After Sleeve Gastrectomy and Roux-en-y Gastric Bypassmentioning
confidence: 99%